2017
DOI: 10.1007/s13337-017-0410-8
|View full text |Cite
|
Sign up to set email alerts
|

In silico comparative analysis of promoters derived from plant pararetroviruses

Abstract: Promoters are specific sequence of nucleotides present upstream of gene coding region involved in initiation and regulation of transcription. Multiple cis-acting element forms the architecture of promoter to which trans-acting nucleic binding factors bind and regulates its activity. Since 1980 genome of pararetrovirus, are being exploited for developing efficient promoters. Among all of them Cauliflower mosaic virus is the most widely used promoter for gene expression. The basic rational behind the strength of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…The highest number of these elements were present in VvGLP2 and -3 promoter. In the same way, unnamed-4 is involved in the regulation of genes controlling various plant processes (Gupta and Ranjan, 2017). The element was largely found in VvGLP4 promoter.…”
Section: Common Cis-regulatory Elementsmentioning
confidence: 95%
“…The highest number of these elements were present in VvGLP2 and -3 promoter. In the same way, unnamed-4 is involved in the regulation of genes controlling various plant processes (Gupta and Ranjan, 2017). The element was largely found in VvGLP4 promoter.…”
Section: Common Cis-regulatory Elementsmentioning
confidence: 95%
“…Sequence analysis using the Plant CARE program [22] showed that the full-length SVBV promoter contained several typical cis-acting elements, such as a TATA box, CAAT box, and potential cis-regulatory elements, including GATA motifs and TC-rich repeats. In previous research, important domains of viral promoters were generally incorporated to generate different mutants, and the driven activities were assessed in tobacco and other plants [23]. According to this prediction, a full-length SVBV promoter from the Chinese isolate (SP1) and three deletion mutants (SP2, SP3, and SP4) were constructed (Fig.…”
Section: Construction Of Expression Vectors Harboring the Full-length...mentioning
confidence: 99%
“…The common promoter motif is the key signature for a family of co-regulated genes and is usually present in the regions where complex protein interactions occur [ 30 ]. It is also reported that genes having similar expression patterns contain common motifs in their promoter regions [ 31 ].…”
Section: Introductionmentioning
confidence: 99%